1999
DOI: 10.1038/sj.onc.1202534
|View full text |Cite
|
Sign up to set email alerts
|

FLI-1 inhibits differentiation and induces proliferation of primary erythroblasts

Abstract: Friend virus-induced erythroleukemia involves two members of the ETS family of transcriptional regulators, both activated via proviral insertion in the corresponding loci. Spi-1/PU.1 is expressed in the disease induced by the original Friend virus SFFV(F-MuLV) complex in adult mice. In contrast, FLI-1 is overexpressed in about 75% of the erythroleukemias induced by the F-MuLV helper virus in newborn mice. To analyse the consequences of the enforced expression of FLI-1 on erythroblast differentiation and prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
79
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 31 publications
(36 reference statements)
8
79
0
4
Order By: Relevance
“…Recently, a similar result was also reported in chicken erythroblasts transfected with Fli-1 (Pereira et al, 1999). Similarly, gp55 expression in HB60-5 cells conferred a growth advantage that was associated with elevated Fli-1 expression levels.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, a similar result was also reported in chicken erythroblasts transfected with Fli-1 (Pereira et al, 1999). Similarly, gp55 expression in HB60-5 cells conferred a growth advantage that was associated with elevated Fli-1 expression levels.…”
Section: Discussionsupporting
confidence: 78%
“…In vitro differentiation studies have shown that in human hematopoietic cell lines, Fli-1 expression promotes MK 34 and suppresses erythroid differentiation. 35,36 The patterns of expression of Ets-1 and Fli-1 were shown to be similar, 28,37 and we found that during 'in vitro' erythroid and MK differentiation, Fli-1 expression profile was superimposable to that of Ets-1 (our unpublished data). Interestingly, the Ets-1 and Fli-1 genes are physically linked, located within 200 kb on human chromosome 11.…”
Section: Discussionmentioning
confidence: 53%
“…In FLV-induced leukemogenesis, the Spi-1 and Fli-1 genes of the host are known to be activated during oncogenesis. These molecules function as transcriptional factors in FLV-induced erythroid leukemic cells and usually inhibit apoptotic cell death in erythroblasts (28,30). However, overexpression of Spi-1 induced growth inhibition, differentiation inhibition, and apoptotic cell death in FLV-induced erythroleukemia cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, human immunodeficiency virus caused apoptosis in CD4 Ï© T cells via gp120 in combination with T cell receptorenhanced (1) and Moloney murine leukemia virus-enhanced thymocyte apoptosis (4). FLV infection usually causes antiapoptotic features in transformed cell lines (14,28,30) as well as in primary erythroblasts (28), although the early effect of FLV infection on apoptotic signaling is still uncertain.The DNA damage induced by gamma irradiation is known to cause p53-dependent apoptosis in many kinds of cells and tissues in vitro as well as in vivo (34). For the purpose of radiotherapy for FLV-induced disease, split low-dose totalbody irradiation (TBI) treatment with 1.5 Gy of gamma irradiation has been performed and shown to exhibit a curative effect on FLV-induced leukemogenesis in DBA mice (36, 37, …”
mentioning
confidence: 99%
See 1 more Smart Citation